CATALASE ACTIVITY OF TWO STREPTOCOCCUS FAECALIS STRAINS AND ITS ENHANCEMENT BY AEROBIOSIS AND ADDED CATIONS - Jones, Dorothy (1964)
Jones, Dorothy (American Meat Institute Foundation, Chicago, Ill.), R. H. Deibel, and C. F. Niven, Jr. Catalase activity of two Streptococcus faecalis strains and its enhancement by aerobiosis and added cations. J. Bacteriol. 88:602–610. 1964.—The nature of catalase activity noted in two unusual Streptococcus faecalis strains was determined. Enzyme activity was lost slowly when cultures were maintained by daily transfer in test tubes of broth media. Loss of activity could be prevented by aerobic culture. Supplementation of the growth medium with ferric, manganese, and zinc ions, as well as aerobiosis, enhanced catalase activity. However, addition of these cations to cell suspensions or to cell-free extracts did not increase catalase activity. Although oxygen was observed to be one of the reaction end products, the catalase activity was not inhibited by cyanide or azide, and the iron-porphyrin coenzyme of classical catalase was not detected. The enzyme was purified 185-fold by precipitation with ammonium sulfate, followed by chromotography on a diethylaminoethyl cellulose column.